Africa. - Westermann, Diedrich, 1875-1956; Forde, Cyril Daryll, 1902-; Smith, Edwin William, 1876-1957 (Oxford University Press, 1928)
Includes Proceedings of the Executive council and List of members, also section "Review of books".